Drawing with a camera? Ethnographic film and transformative anthropology. (31st March 2015) - Grimshaw, Anna; Ravetz, Amanda
Abstract : Drawing has emerged as a recent focus of anthropological attention. Writers such as Ingold and Taussig have argued for its significance as a special kind of knowledge practice, linking it to a broader re‐imagining of the anthropological project itself. Underpinning their approach is an opposition between the pencil and the camera, between 'making' and 'taking', between restrictive and generative modes of inquiry. This essay challenges this assumption, arguing that these elements in drawing and filmmaking exist in a dialectical rather than a polarized relationship. It highlights particular insights that follow from a dialogue between written and film‐based anthropologies and links them to broader debates within the discipline – for example, debates about ways of knowing, skilled practice, improvisation and the imagination, and anthropology as a form of image‐making practice.